The Influence Of Parental Work, Tutoring And Extracurricular On Students' Academic Grades Class X MA Maarif Rejoso Pasuruan Indonesia - Nurus Sobakh; Nunuk Indarti; Sugeng Pradikto (International journal of technology and education research, 2024)
This study aims to find out (1) the influence of parental work on the academic achievement of grade X students of MA Maarif Rejoso (2) the influence of tutoring on the academic grades of students of class X MA Maarif Rejoso (3) the influence of extracurricular activities on the academic grades of students of class X MA Maarif Rejoso (4) the influence of parental work, tutoring and extracurricular on the academic grades of grade X students at MA Maarif Rejoso. The population is 375 students. The sampling technique in this study uses a simple random sampling technique with a sample of 193 students. The data collection method is by questionnaire method. The data analysis in this study uses multiple regression analysis techniques. The results of the study partially show that parental work, tutoring and extracurricular partially on the academic achievement of class X MA Maarif Rejoso Pasuruan are known to have a significant value (sig) of 0.000 < 0.05 which means it has a positive influence on academic scores. The tutoring variable has a significant value (sig) of 0.578 > 0.005 which means it does not have a positive influence on academic scores. The extracurricular variables that were followed had a significant value of 0.000 < 0.05 which means it had a positive influence on academic scores. The results of the simultaneous study showed that parental work, tutoring and extracurricular activities that were partially followed on the academic score of grade X MA Maarif Rejoso were known to have a significant value of 0.000 <0.005 which means that together they have a positive influence on academic scores. The determination coefficient seen in the R Square is 0.831 which means that academic grades are influenced by parental work, tutoring and extracurricular which are followed by 83.1% while the remaining 16.9% is influenced by other factors that are not mentioned and explained in this study.